FAKTOR PENYEBAB KESALAHAN INTERPRETAS RADIOGRAFI KELAINAN DALAM RONGGA MULUT - Muliaty Yunus (DiscoverSys Inc., 2002)
For the interpretation of radiography image a good anddefine was needed radiography result ofthe^best quality.It's purpose have give the image became clearer and itwas formed at the same object and the measureradiography result at the same of the original object.Radiography result is to decrease quality can be etiologyfactors in the interpretation of radiography error. Theother factors can be doing because was not know ofradiography image by normal anatomy structure in oralcavity.The purpose of this paper is to describe etiology factorsinterpretation error of radiography result of intra oralanomaly.